Use of sacral neuromodulation in the treatment of overactive bladder syndrome - Khalid Azzuz, Shahirah; Alosfur, Ziyad Abdulrahman; Alshammari, Abdulrahman Yousef; Alsukaybi, Rakan Hamoud; Alfuhaid, Khalid Salamah; Alanazi, Abdulmajeed Mazi; Alshammari, Abdulaziz Naif; Alanazi, Abdulaziz Fahad; Al-Ghassab, Ali Ahmed; Alenezi, Nayef Khaled; Alrehili, Khalid Ibrahim (International Journal Of Community Medicine And Public Health, 2025)
Overactive bladder syndrome (OAB) is a prevalent condition characterized by urinary urgency, frequency, and incontinence, significantly impacting patients’ quality of life. Sacral neuromodulation (SNM) has emerged as an effective treatment, particularly for individuals unresponsive to conventional therapies. SNM operates by modulating sacral nerve activity to restore normal bladder function, offering both symptom relief and enhanced quality of life. Recent clinical studies demonstrate its long-term efficacy, with sustained improvements in urgency and frequency, and high patient satisfaction rates. Mechanisms underlying SNM involve the modulation of peripheral and central nervous pathways, normalizing overactive detrusor activity and rebalancing excitatory and inhibitory neural signals. Advances in device technology, including rechargeable systems and adaptive stimulation, have further optimized its clinical utility. Minimally invasive techniques and improved electrode designs have enhanced the safety and accessibility of SNM, reducing complications and recovery times. Emerging applications of SNM extend beyond OAB, showing potential in managing neurogenic bladder, fecal incontinence, and chronic pelvic pain. Integration with digital health technologies allows for remote monitoring and personalized adjustments, improving patient outcomes and adherence. Future directions include exploring combined therapies, expanding indications, and leveraging machine learning for tailored neuromodulation. As innovations continue to refine SNM, its role in treating complex pelvic disorders is set to expand, offering a durable, effective solution for patients with refractory conditions. This evolution highlights SNM’s transformative potential in both urological and multidisciplinary care.